Kerukunan Beragama Dalam Lensa Pengalaman Keagamaan Versi Joachim Wach - Taufik Hidayatulloh; Theguh Saumantri (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Religious harmony in Indonesia is a complex phenomenon that involves understanding and religious experiences from various traditions and beliefs. In the thought of Joachim Wach, religious experiences play a crucial role in shaping individual religious identity and providing a foundation for beliefs and religious practices. This research aims to analyze Joachim Wach’s thoughts on religious experiences and their relevance to religious harmony in Indonesia. The study employs a qualitative approach, analyzing primary sources from Joachim Wach’s works and related research. The findings of this research indicate that Joachim Wach’s ideas have contributed to understanding and strengthening religious harmony in Indonesia. In his thinking, Wach identifies three forms of religious experience: through thought, action, and fellowship. Additionally, Wach develops the concept of the “sacred canopy,” which refers to how religion can serve as a framework or framework that provides meaning and significance in human life. Through the concept of “sacred canopy” and understanding of tolerance, society can better understand other religions and strengthen the positive values of each religion. Kerukunan beragama di Indonesia merupakan fenomena kompleks yang melibatkan pemahaman dan pengalaman keagamaan dari berbagai tradisi dan keyakinan. Dalam pemikiran Joachim Wach, pengalaman keagamaan memiliki peran penting dalam membentuk identitas keagamaan individu dan memberikan landasan bagi keyakinan dan praktik agama yang dijalankan. Penelitian ini bertujuan untuk menganalisis pemikiran Joachim Wach tentang pengalaman keagamaan dan relevansinya dengan kerukunan beragama di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan menganalisis sumber-sumber primer dari karya-karya Joachim Wach dan penelitian terkait. Hasil penelitian menunjukan bahwa pemikiran Joachim Wach telah memberikan kontribusi dalam memahami dan memperkuat kerukunan beragama di Indonesia. Dalam pemikirannya, Wach mengidentifikasi tiga bentuk ekspresi pengalaman keagamaan, yaitu dalam bentuk pemikiran, perbuatan, dan persekutuan. Selain itu, Wach mengembangkan konsep “sacred canopy” yaitu konsep tentang bagaimana agama dapat menjadi sebuah kerangka atau bingkai yang memberikan arti dan makna dalam hidup manusia. Melalui konsep “sacred canopy” dan pemahaman tentang toleransi, masyarakat dapat memahami agama lain dengan lebih baik dan memperkuat nilai-nilai yang positif dari setiap agama.